Olympic Games 2020: Discourse of the Japanese government after postponed in japantimes.co.jp - Susilo, D.; Putrantoi, T. D. (Jurnal Kajian Media, 2021)
The COVID-19 outbreak had succeeded in making the holding of the 2020 Tokyo Olympic Games postponed. This became heartbreaking news when Japan was almost ready to host the 32nd Olympic Games. This was the second in Japan during the Olympic Games, held in the 1940 Olympic Games but had to be canceled because Japan was still at war with China since 1937. This research aims to determine the Japanese Government's discourse on the 2020 Olympic Games in the mid of the COVID-19 outbreak after postponed. The method used in this research is the analysis of van Dijk's critical discourse on online news in japantimes.co.jp after the implementation of the Tokyo 2020 Olympic Games was finally announced on 24 March 2020 to be postponed. The findings in this study are that during the 2020 Olympic Games postponement, the Japanese Government tried to use the time to stabilize economic conditions during the 19th COVID outbreak and use the time to make the Tokyo Olympic Games become the most incredible Olympic Games event of all time.